Creating climate coalitions: mass preferences for compensating vulnerability in the world’s two largest democracies - Gaikwad, N; Genovese, F; Tingley, D (Cambridge University Press, 2022)
Combating climate change requires large economic adjustments with significant distributional implications. To build coalitions of support, scholars and policy makers propose compensating individuals who will bear decarbonization’s costs. What are the determinants of public opinion regarding climate compensation and investment? We theorize that climate policy vulnerability and climate change vulnerability induce support for distinct types of climate policy. Fielding original surveys in the United States and India, we show that people who reside in coal-producing regions prefer compensation for lost jobs. The general public privileges diffuse redistribution mechanisms and investments, discounting compensation to targeted groups. Those who are both physically and economically vulnerable have cross-cutting preferences. Nevertheless, there is considerable support across our samples for policies that compensate different coalitions of climate-vulnerable citizens, in line with theories of “just energy” transition and embedded liberalism. We trace the distinctive compensatory preferences of fossil fuel communities to a logic of shared community identities.